Incidencia de la interculturalidad en la convivencia de los estudiantes de los décimos años de educación general básica de la Escuela Mariscal Sucre del cantón Saquisili - Caisaguano Negrete, Julio Cesar (2015)
This rescrach aims to be an important support for intercultural education in “Mariscal Sucre" school, about a recreational activities program. The training establishes three projects with several actions that allows students to work in teams, interacting with classmates, and at the same time the objective is to improve the coexistence of students with different customs and traditions. To observe children interrelating among them, it is an image that should not miss at school because it is a motivation for the existence of a change in the social structure. Now days there is on changing and discriminatory world so it was very important the investigation of the students in the tenth year, the problem was found on students relationship, therefore the principles and values of the human being are promoted for a good life, to this daily struggle the teaching staff of this establishment joined to the project, to ensure that students grow with respect and social awareness. An education with a good social relationship is vital for a meaningful learning, allowing students happiness in their school world where the teacher walk parallel to them being a guide to share experiences and non impose their thinking.